Management Knowledge and Standard Operating Systems in Formulating Company Development Strategies - Ermawati, Emmy (Jurnal Ilmu Manajemen Advantage, 2020)
This study aims to determine the importance of management science and company operational standardization that is applied, to know a good and correct company development strategy in accordance with operational standards of company development strategy at UD. AQMARINA. This type of research is descriptive research with a qualitative approach where the data obtained from a UD. AQMARINA in the form of observation, interviews and literature study. The data used is primary data, where the data is processed from interview data of company owners and publications. The results of this study state that the importance of management knowledge and company operational standards for strategy development is very necessary, this is because the process of organizing something is done by a group of people ororganizationto achieve these goals by working together to utilize the available resources by developing strategies. The standardization of company operations that is applied to this company is very standard, therefore it is necessary to have guidelines on the company's operational system so that it can run the company optimally. A good and correct company development strategy according to operational standards, this is done to get quality human resources with skills, work abilities, and job loyalty to a company or organization. The company's development strategy is not only skill development but also products produced in the form of product variants which are of course creative and innovative.